2021
DOI: 10.31869/mi.v15i1.2487
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perputaran Modal Kerja, Likuiditas Dan Leverage Terhadap Profitabilitas (Studi Kasus Pada Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh perputaran modal kerja, likuiditas dan leverage terhadap profitabilitas pada perusahaan makanan dan minuman yang terdaftar di bursa efek indonesia Periode 2014-2018. Profitabilitas adalah kemampuan perusahaan dalam menghasilkan laba.Dalam analisis rasio, kemampuan menghasilkan laba dapat dikaitkan dg penjualan, aset atau modal. Apabila perusahaan menghasilkan profitabilitas yang tinggi, maka perusahaan akan banyak diminati oleh para investor untuk berinvestas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The existence of CSR is expected to give a positive signal about the company's prospects in the future. The results of previous research conducted by Arita (2019) showed that liquidity influences CSR. In a study conducted by Endiana(2019), value.…”
Section: Csr Mediates the Relationship Between Liquidity And Firm Valuementioning
confidence: 90%
See 1 more Smart Citation
“…The existence of CSR is expected to give a positive signal about the company's prospects in the future. The results of previous research conducted by Arita (2019) showed that liquidity influences CSR. In a study conducted by Endiana(2019), value.…”
Section: Csr Mediates the Relationship Between Liquidity And Firm Valuementioning
confidence: 90%
“…Companies that can fulfill everything on time can be said that the company is in a liquid condition (Sekarwigati, 2019). Research conducted by Arita and Mukhtar (2019) shows that liquidity has a significant effect on csr.…”
Section: Liquidity Affects Csrmentioning
confidence: 99%
“…Corporate Social Responsibility merupakan komitmen perusahaan dalam menjalankan kegiatan operasinya untuk memberikan kontribusi positif terhadap masyarakat sosial dan lingkungan didalam kehidupan sehari-hari [5]. Tingkat produksi yang tinggi adalah umum di industri makanan dan minuman, usaha ini juga menghasilkan limbah yang dibuang ke lingkungan selama proses produksinya.…”
Section: Pendahuluanunclassified
“…On the other hand, having a large inventory and extending credit to customers on sales can increase a company's sales volume. According to Rahmaita & Nini (2021), the working capital turnover rate reflects the extent to which working capital is used effectively within the company, where the higher the working capital turnover rate, the more efficiently the working capital is used. When working capital rotates quickly, companies have greater opportunities to increase profitability.…”
Section: Introductionmentioning
confidence: 99%